PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERORIENTASI SCIENTIFIC APPROACH UNTUK MENUMBUHKAN KEMAMPUAN HIGHER ORDER THINKING (HOT) POKOK BAHASAN PERSAMAAN LINGKARAN PADA SISWA SMA KELAS XI - Utari, Tri; Hobri, Hobri; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to produce valid, effective and practicality students’ mathematics work sheet oriented to Scientific Approach to grow High Order Thinking ability in circle equation subject of eleventh grade senior high school. Research type which is used is Plomp’s development research model. Plomp’s development phases consists of 4 phase which are, (1) initial investigation phase; (2) designing phase (3) realisation/construction phase (4) test, evaluation, and revision phase. Subject which is developed is circle equation. Test done to 34 eleventh grader students of XI MIPA 4 MAN 1 Jember .Validation result for students work sheets show that validity cofficient for LKS is 3,69 so students work sheet has valid interpretation category. Students’ activity achievement level at first to third meeting are 84,89%, 82,81%, and 91,67% with very good category for every meeting. Teachers activity percentation at first to third meeting are 85%, 88,33% and 90% with category very good for every meeting. Analysis data learning result showed leaning result completness is 79,41% and students fulfilled 75 to 100 minimum score, while for stuents’ respond questionnaire to every statements components score 93,66% for students who given positive respon. So this mathematics students’ worksheet oriented to scientific approach to grow High Order Thinking ability in circle equation subject of eleventh grade senior high school has fulfilled validity, effectiveness and practicality. Keyword: Student Worksheet, Scientific Approach, Higher Order Thinking